Travel Writings on Asia Curiosity, Identities, and Knowledge Across the East, c. 1200 to the Present - Mueller, Christian; Salonia, Matteo (Palgrave Series in Asia and Pacific Studies, 2022)
XIV, 310 p. 3 illus., 1 illus. in color.